Illiquidity transmission from spot to futures markets - Olaf Korn; Paolo Krischak; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2017)
We develop a model of illiquidity transmission from spot to futures markets that formalizes the derivative hedge theory of Cho and Engle (1999). The model shows that spot market illiquidity does not translate one to one to the futures market but, rather, interacts with price risk, liquidity risk, and the risk aversion of the market maker. The model's predictions are tested empirically with data from the stock market and markets for single-stock futures and index futures. The results support our model and show that the derivative hedge theory provides an explanation for the liquidity link between spot and futures markets.
Keywords: G10; G13; 330; illiquidity; liquidity risk; futures markets